2019
DOI: 10.1097/mao.0000000000002256
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Characteristics of Internal Auditory Canal Diverticula

Abstract: Hypothesis: We hypothesize that internal auditory canal (IAC) diverticula occur independent of otosclerosis as demonstrated by temporal bone histopathology. Background: Diverticula at the anterior-inferior aspect of the internal auditory canal have been described histologically in the setting of cavitary otosclerosis. Recent radiographic studies show the prevalence of IAC diverticula that is higher than what can be accounted for by cavitary otosclerosis alone. Methods: We examined hematoxylin and eosin tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Hearing results were not significantly different between the two sides. These findings are in accord with prior studies, which have found that IAC diverticula are unrelated to hearing loss 9–11 …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Hearing results were not significantly different between the two sides. These findings are in accord with prior studies, which have found that IAC diverticula are unrelated to hearing loss 9–11 …”
Section: Discussionsupporting
confidence: 92%
“…In a large imaging series, this site was shown to be the most common location of cavitary otosclerosis 13 . Notably, IAC diverticula have also been shown to exist independently from otosclerosis in adults, supporting our theory that higher prevalence in adults is a result of the inclusion of both congenital and acquired diverticula 10 …”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations